An evaluation of the functions of the City Council of George Town Penang 1957-1966 - Awang, Mat Lazim (Universiti Sains Malaysia., 1974)
The main idea of writing this academic exercise is to fulfill the requirements as a compulsory paper, Praotioum on local Historioal Problem of Malaysia,for final year history of the Penang City Council until 1966.The second part deals with the disoussion on the objectives of the local goverment,and the aim is to aoquaint the readers with the structure of the local goverment in Malaysia.